The psychology book - Collin, Catherine (Clinical psychologist); Benson, Nigel C., 1955-; Ginsburg, Joannah; Grand, Voula; Lazyan, Merrin; Weeks, Marcus (Big ideas simply explained., 2024)
"Exploring and explaining the big ideas and groundbreaking theories in psychology clearly and simply, The Psychology Book answers these questions and more and is the perfect introduction to the subject. Untangling knotty theories and shedding light on abstract concepts, entries unpack each complex idea with easy-to-follow explanations and eye-catching images. " -- Amazon.com